2020
DOI: 10.1186/s13063-020-04445-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant dressing therapy versus standard wound care in chronic wounds (the REOX study): study protocol for a randomized controlled trial

Abstract: Background: A wound that does not heal in the orderly stages of the healing process or does not heal within 3 months is considered a chronic wound. Wound healing is impaired when the wound remains in the inflammatory stage for too long. A range of factors can delay the healing process: imbalance between proteases and protease inhibitors in the wound bed; bacterial colonization and the presence of biofilm; and oxidative stress. Recently, wound management has improved significantly. A new antioxidant dressing ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The result of the D. bulbifera extract/honey-loaded Gan/XG correlated with a previous study showing that the ethanolic extract of D. bulbifera bulbils exhibited antioxidant activity by the DPPH radical scavenging assay [25]. The antioxidant patches are the alternative for treatment of difficult-to-heal wounds because the antioxidants help to manage wound oxidative stress and balance the level of reactive oxygen species [37][38][39].…”
Section: Samples Incubation Time (H) 1 H 2 H 4 H 6 Hsupporting
confidence: 85%
“…The result of the D. bulbifera extract/honey-loaded Gan/XG correlated with a previous study showing that the ethanolic extract of D. bulbifera bulbils exhibited antioxidant activity by the DPPH radical scavenging assay [25]. The antioxidant patches are the alternative for treatment of difficult-to-heal wounds because the antioxidants help to manage wound oxidative stress and balance the level of reactive oxygen species [37][38][39].…”
Section: Samples Incubation Time (H) 1 H 2 H 4 H 6 Hsupporting
confidence: 85%
“…For curcumin + NAC, two observational studies in patients with several type of wounds [48,50] have shown an increase in the percentage of complete healing and a reduction in wound size in patients treated with this combination of antioxidants; so this is one of the most promising therapies. Currently, a RCT is ongoing with the aim to compare the effect on the healing of chronic wounds of an antioxidant dressing with curcumin + NAC with the standard dressing treatment [73].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating curcumin and N-acetyl cysteine carried out in humans, specifically observational case series studies concluded that antioxidant treatment is a suitable therapeutic alternative to achieve wound activation of non-healing wounds [44,46]. A randomized controlled trial is currently being conducted evaluating the effect of an antioxidant dressing with curcumin and N-acetyl cysteine on the healing of chronic wounds compared to standard treatment [69].…”
Section: Discussionmentioning
confidence: 99%